Donald in Mathmagic Land [videorecording (DVD)] - Banta, Milt; Berg, Bill, 1917-2002; Haber, Heinz; Luske, Hamilton S. (Distributed by Buena Vista Home Entertainment, 2007)
This highly acclaimed, Academy Award®-nominated film (Documentary Short Subject, 1959), is one of the most popular and entertaining educational films ever made by Walt Disney. A curious Donald Duck ventures into the wondrous Mathmagic Land, where trees have square roots and rivers are brimming with numbers! During his lively journey, Donald discovers that you can have mirth with math, fun with fractions, and laughs with logic in this fascinating and timeless milestone in Disney's animation legacy.